Aspects of thymic pathologies in paediatric patients. Case study of true thymic hyperplasia and the diagnostic approach - Aleksandra Wietecha-Pikul; Agnieszka Juranek; Ewa Cichocka-Jarosz; Izabella Głodzik; Wojciech Górecki; Edyta Juraszewska; Aleksandra Kiszka-Wiłkojć; Grzegorz Lis; Anna Taczanowska-Niemczuk; Przemko Kwinta (Termedia Publishing House, 2024)
Proliferative lesions of the thymus are very rare in children and represent about 2% of mediastinal tumours. They may result from organ hyperplasia, the presence of cysts, or germinal and epithelial neoplasms. All of them can result in massive enlargement of thymus but differ considerably in terms of course and prognosis. This article presents the case of a 2.5-year-old girl with symptoms of respiratory tract infection not responding to antibiotics and with an enlarged thymus, which transpired to be true thymic hyperplasia. In this example, the details of the multidisciplinary diagnostic approach, differentiation, and treatment modalities in children were discussed. An algorithm of the proceedings, with respect to the child's age, was proposed. Although the described pathologies are casuistic in nature, they indicate a necessity to increase vigilance towards symptoms that persist over a prolonged time with no response to standard treatment, because early diagnosis allows the application of appropriate treatment in advance.